Ethylene/1‐Hexene Copolymerization with A Novel SiO2‐Supported Inorganic and Organic Hybrid Chromium‐based Catalyst. Issue 6 (10th April 2013) - Zhang, Shiliang; Cheng, Ruihua; Dong, Qi; He, Xuelian; Wang, Quntao; Tang, Yan; Yu, Yongling; Xie, Kan; Da, Jianwen; Terano, Minoru; Liu, Boping
Abstract: In this work, ethylene/1‐hexene copolymerization with a novel SiO2 ‐supported inorganic and organic hybrid chromium‐based catalyst was investigated. This catalyst was prepared using the residual surface hydroxyl groups in Phillips catalyst to support bis(triphenylsilyl) chromate (BC) in order to get the merits from two important chromium‐based catalysts namely inorganic Phillips and organic S‐2 catalysts. The influences of addition amount of 1‐hexene and BC were systematically investigated. With increasing 1‐hexene from 0 to 7 vol%, the activity of HCat‐2 catalyst showed a decreasing tendency. Its copolymer also showed the better short chain branches distribution through the temperature rising elution fractionation cross successive self‐nucleation and annealing characterization. Abstract : Ethylene/1‐hexene copolymerization with a novel SiO 2 ‐supported hybrid chromium‐based catalyst is investigated. This catalyst is prepared using the residual surface hydroxyl groups in Phillips catalyst to support bis(triphenylsilyl) chromate in order to attain the merits of two important chromium‐based catalysts, namely inorganic Phillips and organic S‐2 catalysts. The copolymer shows better short chain branch distribution.